Survey of silver nanoparticles (Ag-NPs) effects on blood indices of Rainbow trout (Oncorhynchus mykiss) juveniles - Mina Tavassoli Rudsari; Hamidreza Jamalzadeh; Elmira Mikaeili Agah (Anthropogenic Pollution)
Silver nanoparticles (Ag-NPs) are potentially toxicant substances whose widespread use has raised considerations regarding environmental risks caused by the discharge of those nanoparticles (NPs) into aquatic ecosystems. The aim of this study was to analyze the impact of Ag-NPs on the hematologic parameters Rainbow trout, Oncorhynchus mykiss juvenile. Hematological toxicities of Ag-NPs to rainbow trout juveniles were assessed in four treatment groups: Control (without Ag-NPs), 0.1gr/L Ag-NPs solution (T1), 0.25gr/l Ag-NPs (T2) and 0.5gr/l Ag-NPs (T3). Blood samples were collected from fish after 5 and 10 days of exposure. Analysis of blood parameters in the 5th and 10th days of the experiment showed that the values white blood cells (WBCs) were higher in all treatments than those in the control group (p < /p>